2014
DOI: 10.17576/3l-2014-2002-04
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reading Ability and its Relation to L2 Proficiency of Malaysian ESL

Abstract: Critical reading is an important ability to acquire particularly among college or university students. This study investigated the level of critical reading skills among Malaysian ESL learners at the tertiary level. The motivation for conducting the study is due to the increasing number of claims by employers and educators that most graduates lack the ability to read and think critically. Among the required reading and thinking abilities necessary to read a text critically are the analytical and inference skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The students most frequently mentioned that their capability to know some background information of the text before reading it resulted in increased comprehension of the text they read (32.43% of the responses). The finding is in line with Zin et al (2014) who found the knowledge of the content and text genre crucial for students' meaning construction. The PRF based reading practices emphasize the interactive nature of reading and the constructive nature of comprehension by viewing the previous knowledge of the topic to socially and culturally derived cues of the text which is essential for a higher level of comprehension (OECD 2017).…”
Section: The Students' Attitude Towards the Prf-based Reading Practicessupporting
confidence: 87%
See 1 more Smart Citation
“…The students most frequently mentioned that their capability to know some background information of the text before reading it resulted in increased comprehension of the text they read (32.43% of the responses). The finding is in line with Zin et al (2014) who found the knowledge of the content and text genre crucial for students' meaning construction. The PRF based reading practices emphasize the interactive nature of reading and the constructive nature of comprehension by viewing the previous knowledge of the topic to socially and culturally derived cues of the text which is essential for a higher level of comprehension (OECD 2017).…”
Section: The Students' Attitude Towards the Prf-based Reading Practicessupporting
confidence: 87%
“…Critical reading and thinking are essential for academic achievement in higher education and developing students' critical thinking skills is regarded as a highly important educational goal in many societies around the world (Zin et al 2014, Davies & Barnett 2015, Wilson 2016, Stupplea et al 2017, Larsson 2017. To be successful in class, students are required to read extensively for knowledge and information from textbooks, research articles, and other sources and think critically about what they have read.…”
Section: Introductionmentioning
confidence: 99%
“…Critical reading and thinking are key to academic achievement in higher education and the development of critical thinking skills among students is seen as a very important educational goal in many societies around the world (Zin et al 2014, Davies & Barnett 2015, Wilson 2016, Stupplea et al 2017, Larsson 2017, Khamkhong 2018). Critical reading requires readers to go beyond the literal and interpretive comprehension of reading texts.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the efficient reading skills will serve as toolkits to read the world that could help one to be better student or worker (Zuhana et al, 2014). In academic and working environments setting, students and the readers are constantly need to synthesize, evaluate, interpret and use the information in text selectively.…”
Section: Introductionmentioning
confidence: 99%
“…In academic and working environments setting, students and the readers are constantly need to synthesize, evaluate, interpret and use the information in text selectively. Thus, it is an important thing for them, for instance how to have good analytical skills to evaluate an analyze the information contained in the text they encounter daily (Zuhana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%